The Influence of Perceived Trust on Understanding Banks’ Customers behavior to Accept Internet Banking Services - Al-Sharafi, Mohammed A.; Ruzaini, Abdullah Arshah; Alajmi, Qasim; Herzallah, Fadi A.; Qasem, Yousef A. M. (Informatics Publishing Limited, 2018)
Background/Objectives: The purpose of this paper is to examine the role of trust in internet banking services based on empirical evidence from the survey conducted with commercial banks’ consumers in Irbid, the second largest city in Jordan. The paper answers the main research question: ‘Do the Ease of Use and Perceived Usefulness affect consumers’ trust to accept and use internet banking technology to perform their banking transactions?’ Methods/Analysis: This is an explanatory paper based on literature reviews and empirical data to explore reasons for accepting internet banking service. The approach takes the form of an empirical study conducted with 198 bank’s consumers in the north of Jordan using a basic model of the adoption of internet banking depends on Technology Acceptance Model framework (TAM). Partial Least Squares (PLS) was used to address sophisticated data analysis issues. Findings: The results confirm that trust increases if users perceive internet banking services to be useful whereas perceived ease of use fails to predict Jordanians’ trust to accept and use internet banking services. Novelty/Improvement: The findings from this study are useful for policy makers, banking sectors and financial practitioners to enhance the use of internet banking services among Jordanians.